The recovery of regional geography through a political concept of region - Albuquerque, Edu Silvestre de (GEOUSP Espaço e Tempo (Online), 2001)
The article proposes the retrieve of the regional method, by means of a concept of region applicable to Federal State. The existence of regional state institutions with constitutional autonomy in an ambience of strong regional identity defines accurately the regional object. The transformation of the state solidarity around these autonomous regional institutions in a kind of regional solidarity is also analyzed. This transformation generates regional identities and regionalisms